Immigration Opportunity or Organizational Oxymoron? The Canadian Jewish Farm School and the Department of Immigration, 1925-1946 - Lipinsky, Jack (Canadian Jewish Studies / Études juives canadiennes, 2015)
Examining uniquely dramatic historical narratives often illuminates the much more complex web of issues surrounding them. For example the stories of the Komagata Maru and St. Louis incidents speak volumes about key questions in Canadian immigration history. But less dramatic narratives also serve to illuminate the intricacies of interwar Canadian immigration policy towards Jews. The strange tale of the Canadian Jewish Farm School (CJFS) of Georgetown, Ontario yields fascinating insights into the relationship between Canadian Jews, the Department of Immigration, and Frederick Blair that further illuminates the work of previous historians. It also adds to our knowledge of the intra-Jewish squabbles over immigration strategies and tactics taking place between the wars, and the extent to which these affected Departmental policy.